Penerapan Early Warning Score (EWS) dalam Mendeteksi Dini Perburukan Kondisi Pasien Covid-19 - Dally Rahman; Emil Huriani; Elvi Oktarina (Warta Pengabdian Andalas, 2022)
The high mortality rate of Covid-19 is a problem for the government and health services that were influenced by treatment strategy at the hospital. Covid-19 patients can experience a sudden severe condition without apparent symptoms known as "Silent Hypoxemia". A further severe condition will lead to the sudden death of the patient. Therefore intensive monitoring is needed to prevent this condition. Based on the evidence, the severe level patient's condition can be detected earlier, within 6-8 hours, using the physiological parameters consisting of vital signs in the tools of the Early Warning Score (EWS) for patients. It was not fully known by nurses at hospitals treating Covid-19 patients. The program aims to provide increased knowledge on Early Warning Score (EWS) for Covid-19 patients of Andalas University Hospital's nurses, to create EWS formats and Standard Operational Procedures for EWS Covid-19 patients. Based on the knowledge evaluation of nurses, there was an increase in the average knowledge score of 13 points, with a pre-activity knowledge score of 78 to 91 for post-activity. It was expected that Andalas University Hospital could implement Early Warning Warning Score (EWS) for Covid-19 patients as a Standard Operating Procedure for treating Covid-19 patients.